PENGARUH PENERAPAN GREEN ACCOUNTING DAN MATERIAL FLOW COST ACCOUNTING TERHADAP SUSTAINABLE DEVELOPMENT DENGAN RESOURCE EFFICIENCY SEBAGAI PEMODERASI - Mishelei Loen, SE., M.Si. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2019)
This study aims to determine whether there is a relationship and influence between the application of Green Accounting, Material Flow Cost Accounting (MFCA) on Sustainable Development with Resource Efficiency as moderating. The sample used consisted of thirty-three manufacturing companies. The method used in this study uses quantitative methods. Where the form of this research is descriptive and inferential analysis. Inferential analysis uses purposive sampling and causality analysis. The data used in this study are primary data, using statistical analysis methods and using IBM SPSS Statistics 21 software assistance. The results of the study indicate that the Application of Material Flow Cost Accounting has no positive effect on Sustainable Development. Positive results on the adoption of Green Accounting for Sustainable Development. Resource Efficiency does not oppose Material Flow Cost Accounting towards Sustainable Development. Resource Efficiency positively implements the application of Green Accounting for Sustainable Development.